Écrits politiques 3 : 1923-1926 - Gramsci, Antonio; Paris, Robert; Martin-Gistucci, Marie-Gracieuse; Moget, Gilbert (Paris : Gallimard, 1980)
Bibliotheek François Vercammen
Frans
Meerdelige publicatie
Keywords: Partito Comunista Italiano (PCI).; communisme; Italië